Cover Picture: Understanding the Fundamental Role of π/π, σ/σ, and σ/π Dispersion Interactions in Shaping Carbon‐Based Materials (Chem. Eur. J. 17/2014). Issue 17 (22nd April 2014) - Alonso, Mercedes; Woller, Tatiana; Martín‐Martínez, Francisco J.; Contreras‐García, Julia; Geerlings, Paul; De Proft, Frank
<x xml:space="preserve">Abstract</x> Noncovalent interactions involving aromatic rings, such as π‐stacking and CH/π interactions, are central to many areas of modern chemistry. In their Full Paper on page 4931 ff., M. Alonso et al. describe their investigations on the nature and origin of π/π, σ/σ and σ/π dispersion interactions by using dispersion‐corrected density functional theory, energy decomposition analysis and the noncovalent interaction method. The analysis confirms that π/π and σ/σ stacking interactions are equally important in energy for the benzene and cyclohexane dimers, but different in origin. These new types of dispersion interactions between saturated groups can be exploited in the rational design of novel carbon materials.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>